THE INFLUENCE OF SAMSUNG PRODUCT PLACEMENT IN KOREAN DRAMA â€œCRASH LANDING ON YOUâ€ ON BRAND MEMORY - Kembuan, Kesia F.; Lapian, Stanss L. H. V J.; Wangke, Shinta J. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
People have hundreds of options for any product or service in a crowded marketplace, marketers have had to come up with new ways to get people's attention. One such strategy that marketers have begun to utilize is product placement. This study aims to find out whether the three dimensions of product placement: visual dimension, auditory dimension, and plot connection dimension, influence the brand memory of audiences partially and simultaneously. The study was conducted on 100 students of Faculty of Economics and Business, Sam Ratulangi University using quantitative method and Multiple Linear Regression as the analysis tool. The results revealed the two of three dimensions of product placement which are visual and plot connection, partially has a positive and significant influence on brand memory. In contrast, the auditory dimension partially has no significant influence on brand memory. Simultaneously, all three dimensions of product placement have a positive and significant effect on brand memory. Therefore, Samsung or the other company can explore more the appearance of the auditory dimension and also maintain and improve the other two dimensions, namely the visual and the plot connection dimension, in order to have a greater influence.Â Keywords: product placement, visual dimension, auditory dimension, plot connection dimension, brand memory